Nonlocal ansatze and solutions of a nonlinear system of heat-conduction equations - Amerov, T. K.; Serov, N. I.; Fushchich, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
By a nonlocal substitution, a nonlinear system of heat-conduction equations is reduced to a scalar nonlinear heat-conduction equation. The Lie and conditional invariance of the scalar equation is used to find nonlocal ansatze which reduce the original system to systems of ordinary differential equations.